Perbandingan Kinerja Pengiriman Data Skema Routing Single-Copy dan Multi-Copy pada Jaringan Delay Tolerant Network (DTN) - Fedro Jordie T. H. Simangunsong; Heru Nurwarsito; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowadays the Internet become the most popular way to get and share information. But not all regions in Indonesia have an uninterrupted Internet connection. Rural, mountain climbing, and marine are examples of areas having interrupted Internet connections. These problems can be solved by adapting Delay Tolerant Network (DTN) technology. In this research, the DTN Network was simulated in The ONE Simulator to compare performance of DTN routing scheme with buffer size, message size, and different geographical location. Routing protocols that used are Direct Delivery and First Contact for Single-copy routing schemes, and MaxProp, Spray and Wait, and Epidemic for Multi-copy routing schemes. The results show that the performance of Multi-copy routing scheme is better than Single-copy routing scheme, especially on the Delivery Probability and Average Latency value. With the highest Delivery Probability value of 98.08% compared to 88.56% of Single Copy, the lowest Average Latency value is 40.3138s, compared to 41.2028s of Single-copy, the lowest Overhead Ratio is 367.66%, compared to 0% of Single-copy. MaxProp routing protocol generated the best Delivery Probability value. While, the best Average Latency value generated by Spray and Wait routing protocol. And Direct Delivery generated the best Overhead Ratio value.